2016
DOI: 10.2147/copd.s109227
|View full text |Cite
|
Sign up to set email alerts
|

Illness perceptions and coping determine quality of life in COPD patients

Abstract: BackgroundA key goal of chronic obstructive pulmonary disease (COPD) care is to improve patients’ quality of life (QoL). For outcomes such as QoL, illness perceptions and coping are important determinants.AimThe primary aim was to assess the associations between illness perceptions, coping and QoL in COPD patients. A secondary aim was to compare illness perceptions and coping of patients with reference values derived from the literature.Patients and methodsA total of 100 patients were included in the study. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
1
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 24 publications
6
45
1
8
Order By: Relevance
“…Multivariate linear regression analysis showed that a high perception of illness is an independent predictor of better QOL. These results are consistent with results of previous studies of other chronic illnesses in which better personal control and illness perception were associated with higher physical QOL . Better health literacy and knowledge about the disease and its treatment can improve QOL in patients with chronic diseases …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Multivariate linear regression analysis showed that a high perception of illness is an independent predictor of better QOL. These results are consistent with results of previous studies of other chronic illnesses in which better personal control and illness perception were associated with higher physical QOL . Better health literacy and knowledge about the disease and its treatment can improve QOL in patients with chronic diseases …”
Section: Discussionsupporting
confidence: 91%
“…These results are consistent with results of previous studies of other chronic illnesses in which better personal control and illness perception were associated with higher physical QOL. 30 ALT, alanine transaminase, AST, aspartate transaminase; Hb, hemoglobin. P ≤ 0.05 is significance.…”
Section: Discussionmentioning
confidence: 99%
“…It shows that the better the patient illness perception, the better the QoL, and the opposite. A previous study had the same results, which showed a significant correlation between illness perception and QoL (Nabolsi, Wardam, & Al-Halabi, 2013;Scharloo et al, 2007;Tiemensma et al, 2016). As examples, identity has moderate and negative correlation with vitality domain (r: -0.431; p: 0.001).…”
Section: Discussionsupporting
confidence: 62%
“…A patient's QoL may be influenced by chronic pain, female gender, lower education level, increased BMI, diabetes-related distress and mobility restriction (Kamradt et al, 2017). Furthermore, illness perception and coping, may influence QoL (Tiemensma, Gaab, Voorhaar, Asijee, & Kaptein, 2016). Patients may develop their own perspectives about their health, disease and treatment due to the coping process (Dorrian, Dempster, & Adair, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Whether patients perceived the heart transplantation as a "second chance" and "the gift of life" or as an "exchange of one problem with another", seemed to play an important role in determining the coping strategies they employed and whether they were satisfied or dissatisfied with their postoperative life It is not the nature of an illness that is of uppermost importance, but rather the individual's cognitive appraisal of it (Lazarus, Averill, & Opton, 1974;Buunk, Gibbons, & Buunk, 2013;Tiemensma, Gaab, Voorhaar, Asijee, & Kaptein, 2016). Miller (1986) stated that, if an illness is viewed as significant, heightened anxiety and depression are more likely to manifest themselves in an attempt to cope; if the illness is appraised as insignificant, the client will feel less personally threatened and will have greater energy for dealing with the problems presented by the illness.…”
Section: The Role Of the Perception Of The Demands In Influencing Thementioning
confidence: 99%